الوظيفة الجمالية للنحو في تراثنا النقدي العربي القديم عبد القاهر الجرحاني نموذجاً: The esthetic function of grammar in our ancient Arab critisism heritage- Abdul-Qaher Al-Jorjani as a model - El Marrakchi, Hanan Mohamed (SIBAWAYH Arabic Language and Education, 2020)
In his books “DalaelI”jaz” and “Asraralbalara”, Abdul-Qaher Al-Jorjani represents "the secrets of rhetoric" and "the signs of miracles" in our Arab heritage, the most mature attempts in analyzing literary style or text are based on his understanding of the function of grammar in the speech system and the production of the significance. He was guided by the fact that any literary statement is language-based but has identifiable characteristics, which he enters within the limits of art, which implicitly distinguishes between language in the sense of a well-established grammar system in the consciousness of the community and speech in the sense of the actual realization of these laws in a particular speech. The poet’s lexical work - for example - with the language similar to that of the manufacturer’s relation with its raw material, the latter does not start the subject of words or its meaning, but reforms the humble words on them in new relationships, producing a form that affects its significance, and who is given its eloquent communication. The poet is not only standing at this point, but her own example extends to the semantics that Abdul Qaher calls “ meanings of the grammar” .The research seeks to reveal the grammar theory of Abdul Qaher Al-jorjani, which came in introduction, three chapters, and conclusion. The first: Abdul Qaher Al-Jorjani and his grammar philosophy. Second: The role of grammar in the production of significance.The third: Creative grammar relationships.